Adolescents with or at ultra‐high risk for bipolar disorder exhibit erythrocyte docosahexaenoic acid and eicosapentaenoic acid deficits: a candidate prodromal risk biomarker. Issue 3 (20th October 2015) - McNamara, Robert K.; Jandacek, Ronald; Tso, Patrick; Blom, Thomas J.; Welge, Jeffrey A.; Strawn, Jeffrey R.; Adler, Caleb M.; Strakowski, Stephen M.; DelBello, Melissa P.
Abstract: Aim: Mood disorders are associated with low levels of the long‐chain omega‐3 (LC n ‐3) fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). This study investigated LC n ‐3 fatty acid biostatus in youth with or at varying risk for developing mania to assess its utility as a prodromal risk biomarker. Method: Erythrocyte fatty acid composition was determined in healthy adolescents ( n  = 28, HC), asymptomatic adolescents with a biological parent with bipolar I disorder ( n  = 30; 'high risk', HR), adolescents with a biological parent with bipolar I disorder and major depressive disorder, or depressive disorder not otherwise specified ( n  = 36; 'ultra‐high risk', UHR), and first‐episode adolescent bipolar manic patients ( n  = 35, BP). Results: Group differences were observed for DHA ( P  ≤ 0.0001) and EPA ( P  = 0.03). Compared with HC, erythrocyte EPA + DHA ('omega‐3 index') was significantly lower in BP (−24%, P  ≤ 0.0001) and UHR (−19%, P  = 0.0006) groups, and there was a trend in the HR group (−11%, P  = 0.06). Compared with HC (61%), a greater percentage of HR (77%, P  = 0.02), UHR (80%, P  = 0.005) and BP (97%, P  = 0.001) subjects exhibited EPA + DHA levels of ≤4.0%. Among all subjects ( n  = 130), EPA + DHA was inversely correlated with manic ( r  = −0.29, P  = 0.0008) and depressive ( r  = −0.28, P  = 0.003) symptom severity. The AA/EPA + DHA ratio was significantly greater in BP (+22%, P  = 0.0002) and UHR (+16%, P  = 0.001) groups. Conclusions: Low EPA + DHA levels coincide with the initial onset of mania, and increasing risk for developing bipolar disorder is associated with graded erythrocyte EPA + DHA deficits. Low erythrocyte EPA + DHA biostatus may represent a promising prodromal risk biomarker warranting additional evaluation in future prospective studies.